2021
DOI: 10.1249/mss.0000000000002605
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Lower Limb Muscle Characteristics and Force–Velocity Profiles Derived during Sprinting and Jumping

Abstract: Purpose: This study aimed to identify the relationships between lower limb muscle characteristics and mechanical variables derived from the vertical (jumping) and horizontal (sprinting) forcevelocity-power (FVP) profiles. Methods: Nineteen subelite male rugby league players performed a series of squat jumps and linear 30-m sprints to derive the vertical and horizontal FVP profiles, respectively. The theoretical maximal force (F 0 ), velocity (V 0 ), and power (P max ) were derived from both the vertical (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…It has been reported that maximal muscle power in jumping and sprinting are positively correlated with lower limb muscle volume, especially the vastus medialis muscle. 2 In general, muscle thickness in the distal medial femoris is larger in men than in women. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that maximal muscle power in jumping and sprinting are positively correlated with lower limb muscle volume, especially the vastus medialis muscle. 2 In general, muscle thickness in the distal medial femoris is larger in men than in women. 5 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that maximal muscle power in jumping and sprinting are positively correlated with lower limb muscle volume, especially the vastus medialis muscle. 2 In general, muscle thickness in the distal medial femoris is larger in men than in women. 5 There was significant difference in the rate of button malposition according to the surgeon experience group (40.9% for low-volume vs 18.1% for medium-volume vs 10.2% for high-volume surgeons; P ¼ .003).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the repetition of high-velocity knee flexion movements during sprinting might induce preferential hypertrophy of ST in sprinters. Regarding the preferential hypertrophy of BFsh in sprinters, recent research reported that muscle volume of BFsh (together with fiber typology of gastrocnemius medialis) could explain ~59% of the theoretical maximal horizontal velocity derived from linear 30-m sprints [ 22 ]. This finding implies that BFsh greatly contributes to the generation of horizontal velocity during acceleration phase of sprint running (e.g., approximately 0–30 m).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is inconsistent with our hypothesis that muscle size of RF is larger in sprinters than in rugby players. Recent research indicated that muscle volumes of RF and VL could explain ~43% of the theoretical maximal vertical force derived from jumping and suggest that muscle sizes of RF and VL significantly contribute to a generation of a vertical force at low angular velocity [ 22 ]. This finding allows us to speculate that the preferential hypertrophy of RF and VL in rugby players may be caused by competitive actions that require a generation of a large vertical force at low movement velocity rather than the actions that require a production of a large horizontal force at high movement velocity like sprint running.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, the MFT of team-sport athletes has received less attention. 18 Many team sports require athletes to produce maximal and/or near-maximal efforts including accelerating, sprinting, changing directions, which are interspersed with brief recovery or passive periods, often over an extended period of time (ie, matches that last >60 min). 19 Defining performance in most team sports is difficult (ie, technical and tactical considerations); however, superior athletic performance (ie, strength, speed, and endurance) are undoubtedly underpinning characteristics associated with successful performance.…”
mentioning
confidence: 99%